Some biological aspects of the spotted snakehead Channa punctata (Bloch, 1793) in the wetland ecosystem, Gajner Beel, North-western Bangladesh - Afroz Chowdhury, Asma; Hossain, Md. Yeamin; Mawa, Zannatul; Khatun, Dalia; Islam, Md. Akhtarul; Rahman, Md. Ataur; Hasan, Md. Rabiul; Rahman, Obaidur; Konok, Redwanul Haque; Rahman, Md. Ashekur; Parvin, Most. Farida; Sarkar, Uttam Kumar (Indian Journal of Fisheries, 2021)
Documenting and updating life history traits of wild fish are prerequisite for undertaking any conservation and enhancement programme from inland waters. The spotted snakehead Channa punctata (Bloch, 1793) is an important small indigenous food fish in Asian countries which has high nutritional and commercial value. This is the first work on describing life-history traits including growth pattern, condition factors (Fultonâ€™s, KF; Allometric, KA; Relative condition, KR; Relative weight, WR), form factor (a3.0), size at first sexual maturity (Lm) and natural mortality (Mw) in the Gajner Beel, northwestern Bangladesh during July 2018 to December 2019. Traditional fishing gears were used for sampling. Different lengths (i.e., total length, TL; standard length, SL) and body weight (BW) of each individual were taken using digital slide calipers and an electronic balance to the nearest 0.01 cm and 0.01 g, respectively. In total, 583 individuals ranging from 5.8-22.8 cm TL and 1.96-115.08 g BW were collected in this study. On the basis of b value, the growth pattern of C. punctata was isometric (b=3.0) in all the LWRs. Also, all LWRs were highly significant with r2 values â‰¥0.979. The LLR was highly significant (p<0.001) with r2 =0.992. Among the four types of condition factor, KF showed highly significant relationship with TL and BW (p<0.001). Therefore, KF considered the best for assessing the overall health of this species in the Gajner Beel, NW Bangladesh. Wilcoxon Signed rank test showed that, WR was not significantly different from 100 (p=37235). Also, the calculated a3.0 was 0.0111, which indicates the fish was fusiform in shape. Moreover, the Lm and Mw were 12.67 cm TL and 0.96 year-1 , respectively. Therefore, the findings of this study would serve as baseline for stock assessment of floodplain wetland population and sustainable management of wild C. punctata in Gajner Beel and adjoining watershed. Keywords: Channa punctata, Condition factor, Gajner Beel, Natural mortality, Size at first sexual maturity, Wetland